Koagulopatie asociovaná s onemocněním COVID-19 - Bílková, Simona; Hirmerová, Jana (Vnitrni lekarstvi, 2020)
Infection with a new type of coronavirus surprised with the diversity of its clinical symptoms. The disease may be asymptomatic, with only mild symptoms in the form of olfactory loss, general weakness or flu-like symptoms. However, in some patients, COVID-19 infection can be severe, with hypercoagulation being a common finding, with vascular endothelial damage and the consequent risk of venous and arterial thrombotic complications. Coa-gulopathy subsequently significantly worsens the prognosis of patients and increases overall mortality. Recently, a new term has been introduced to indicate the presence of activated hemostasis in SARS-CoV-2 infection - coagulopathy associated with COVID-19 (CAC). The current global pandemic of COVID-19 has triggered intensive research on the disease, which has clarified a number of findings about the infection, but we still have many unanswered questions, especially regarding possible treatment.
Keywords: Heparin; Blood Coagulation Disorders; koagulopatie; heparine; liver cirrhosis; Coagulopathy; immuno-trombosis; koronavirové infekce; Pandemics; lidé; Coronavirus Infections; D-dimers; pandemie; Humans; COVID-19; SARS-CoV-2